Environmental Regulation, Environmental Decentralization, and Enterprise Environmental Protection Investment: Evidence From China - Liu, Li; Ren, Guangqian; He, Banghua; Zheng, Minna (Frontiers in Public Health, 2022)
The microeconomic behavior of enterprises is influenced by the government system and its policies. In this paper, we investigate how environmental regulation and environmental decentralization affect enterprise environmental protection investment using the data of China’s listed companies from 2009-2020 and examine the effect of environmental decentralization on the relationship between environmental regulation and environmental protection investment. Firstly, we find that there is a ‘U-shaped’ relationship between environmental regulation and enterprise environmental protection investment. Secondly, the estimation results indicate that environmental decentralization can promote enterprise environmental protection investment. Finally, we further provide evidence to show that environmental decentralization have a negtive moderating impact on the relationship between environmental regulation and enterprise environmental protection investment. Accordingly, The conclusion of this study is helpful to optimize the environmental decentralization management system, reasonably guide the local government behavior, alleviate the contradiction between environmental protection and economic development, and promote the green transformation of economic development mode.